ANALISIS TINGKAT KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA BANJIR DI KECAMATAN MEUREBO KABUPATEN ACEH BARAT - Saifuddin, Indra, Hermansyah. (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2015)
Abstract: West Aceh District, particularly the Meureubo subdistrict, is one area that often experienced floods. Various trainings and socializations have been conducted by the Regional Disaster Management Agency (BPBD) as well as the stakeholders in improving community preparedness. The objective of this study was to determine the level of community preparedness in facing disastrous floods in Meureubo subdistrict in West Aceh district. This study used multiple linear regression design of quantitative approach that had been carried out in June 2015. The population of this study was the society of Meureubo subdistrict of West Aceh district; consisting of 3 villages (Gampong), namely Pasie Mesjid village, Ranto Panyang Barat village and Pulo Teungoh village, with a total of 509 householders, while the chosen sample was 85 people who had experienced floods disaster. The results showed that the level of public knowledge in dealing with floods disaster is not good (65.9%) and good (34.1%). The majority of respondents’ attitude is negative, as many as 53 people (62.3%), and the level of preparedness of the majority of respondents is less prepared (39%). The statistical results obtained showed that there is a significant influence between knowledge (p = 0.001) and attitude (p = 0.003). It can be concluded that the level of community preparedness in dealing with flood disaster in Meureubo subdistrict is considered less prepared due to the influences of both attitude and knowledge towards the community preparedness in dealing with floods. Therefore, the measures and strategies to improve the public knowledge and build the positive attitude of the society in dealing with flood disaster are necessary to be conducted sustainably.Keywords : :knowledge, attitude, preparedness, and floods Abstrak: Kabupaten Aceh Barat khususnya Kecamatan Meureubo merupakan salah satu daerah yang sering terjadi banjir. Berbagai pelatihan dan sosialisasi telah dilakukan oleh Badan Penanggulangan Bencana Daerah (BPBD) maupun stakeholder dalam peningkatan kesiapsiagan di masyarakat. Tujuan penelitian ini untuk mengetahui tingkat kesiapsiagaan masyarakat dalam menghadapi bencana banjir di Kecamatan Meureubo Kabupaten Aceh Barat. Penelitian ini menggunakan desain Regresi Linear Berganda yang menggunakan pendekatan kuantitatif, dilaksanakan pada bulan Juni 2015. Populasi dalam penelitian ini adalah semua masyarakat Kecamatan Meureubo Kabupaten Aceh Barat yang terdiri dari 3 Gampong yaitu Gampong Pasie Mesjid, Ranto Panyang Barat dan Pulo Teungoh dengan jumlah kepala keluarga 509 KK, dengan besar sampel sebanyak 85 orang yang mengalami banjir. Hasil penelitian menunjukkan bahwa tingkat pengetahuan masyarakat dalam menghadapi bencana banjir adalah kurang baik (65,9%) dan baik (34,1%) , sikap responden mayoritas negatif yaitu sebanyak 53 orang (62,3%), dan tingkat kesiapsiagaan mayoritas kurang siap (39%),. Hasil statistik diperoleh ada pengaruh yang bermakna antara pengetahuan (p=0,001), dan sikap (p=0,003). Maka dapat disimpulkan bahwa tingkat kesiapsiagaan masyarakat dalam menghadapi bencana banjir di Kecamatan Meureubo masih kurang siap karena antara sikap dan pengetahuan ada pengaruh terhadap kesiapsiagaan masyarakat dalam menghadapi bencana, untuk itu dibutuhkan langkah-langkah dan strategi dalam peningkatan pengetahuan dan perubahan sikap positif masyarakat secara berkelanjutan.Kata kunci : pengetahuan, sikap, kesiapsiagaan, dan banjir